(untitled) - Phạm, Thị Hồng Nhung (Cần Thơ, 2011)
This study in investigated the effects of the speaking task used as an output task on high school students’ vocabulary retention. The results also proved that the students had positive attitudes towards the speaking task used as an output task in teaching and learning vocabulary. This implies that the speaking task used as an output task can help improve high school students’ vocabulary retention and can be preferred by high school students
Keywords: Learning vocabulary,Học từ vựng